Corporate social responsibility and organizational commitment of semiconductor companies in Kulim High Tech Park, Kedah : Employees perspectives - Seah, Yett Ming (2014)
The fact that corporate social responsibility has been an increasing focus in today‟s business world cannot be denied. Numerous organizations have started to understand that they should adopt corporate social responsibility practices as a strategy to gain and sustain their competitive advantages. Due to the little attention given to CSR strategies related to employee‟s commitment until recent years, Malaysia has remained largely unexplored. The aim of this research is to investigate the influences of Corporate Social Responsibility (CSR) toward organizational commitment in Malaysia. This study will investigate CSR through four dimensions of responsibilities, namely, economic responsibility, law responsibility, ethically responsibility and discretionary responsibility. Social exchange theory and social identity theory will help explore the preferences toward CSR dimensions, and to identify relationship between CSR and organizational commitment. This study was conducted in semiconductor companies at Kulim High Tech Park in Kedah. The model was tested on a sample of 150 executive officers working in Kulim High Tech Park. Findings indicated a significant positive relationship between CSR practices and employee organizational commitment. Meanwhile, ethical responsibility was the most significantly related of the factors to influencing organizational commitment. Organizations should emphasize the CSR action for enhancing employee‟s organizational commitment and improving organizational performance by emphasizing more on ethical actions related to CSR activities.